THE UTILIZATION OF PLEDGED GOODS IN ISLAMIC JURISPRUDENCE: A COMPARATIVE ANALYSIS OF CLASSICAL SCHOLARLY PERSPECTIVES AND IMAM SHAFI'I'S LEGAL FRAMEWORK: Rahn, Utilization of Pledged Goods, Imam Shafi'i - Wan Rahmat Agustian; Kartubi; Januariusdi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The utilization of pledged goods (rahn) in informal Muslim community transactions in Indonesia remains widely practiced yet legally unexamined, creating a normative gap between community convention and classical Islamic jurisprudence. This study aims to analyze Imam Shafi'i's precise legal reasoning on the utilization of pledged goods and to comparatively situate his position against the Hanafi, Maliki, and Hanbali schools. Employing a qualitative approach with a case study design, data were collected through library research on classical fiqh texts and analyzed using the interactive model of Miles, Huberman & Saldaña. The study finds that Imam Shafi'i categorically prohibits any creditor utilization of pledged goods, classifying it as riba regardless of mutual consent, asset type, or pledge duration, grounded in the principle that ownership and its benefits remain exclusively with the pledgor. Comparatively, the Hanafi school permits utilization upon explicit consent, the Maliki school allows limited animal use proportionate to maintenance, and the Hanbali school grounds animal-use permissibility in prophetic authority. These divergences reflect fundamental differences in jurisprudential methodology across the four schools. The findings provide doctrinal clarity essential for protecting economically vulnerable communities from exploitative informal financial arrangements, directly contributing to SDG 1, SDG 10, and SDG 16.